Epidemiology and risk factors in osteoarthritis: literature review data from “OASIS” study - L. De Filippis (Reumatismo, 2004)
Ostheoarthritis (OA) is a social disease characterized by pain, inflammation and stiffness due to an involvement of articular cartilage, soft tissues and bone.OA is the most common rheumatic disease, every age can be affected but prevalence increases dramatically with age with a greater incidence in subjects between 40 and 50 years of age. Hip OA has an important correlation with weight, genetic factors, sex, previous traumas, occupational factors and age. People older than 35 have a prevalence of Hip OA of 10,8% that becomes 35,4% in people older than 85. Knee OA has a great correlation with weight ,life style and physical activity. An Italian study has demonstrated that the prevalence of this kind of OA is highest in subjects older than 65 that becomes 44% in people older than 80. In this report we explain the results of a study conducted in the South of Italy called the OstheoArtrithis Southern Italy Study (OASIS) that involved 456 doctors and 1782 patients of three different regions.The mean age of these patients was 66,3 years and we evaluated prevalence of hip, knee, hand and spine OA and correlated it to sex, age, weight and BMI. We also evaluated what kind of drugs were used for these patients. Knee OA is the most common subset of OA, the one that requires the highest number of examinations and the one that causes the greatest disability.The most common used drugs are Fans and Coxibs. Condroprotectors were not used much, probably because they are not considered to be very effective.